2010
DOI: 10.1645/ge-2180.1
|View full text |Cite
|
Sign up to set email alerts
|

Stomach Nematodes (Mastophorus muris) in Rats (Rattus rattus) Are Associated with Coconut (Cocos nucifera) Habitat at Palmyra Atoll

Abstract: Black rats ( Rattus rattus ) and their stomach nematodes (Mastophorus muris) were historically introduced to islets at Palmyra Atoll in the central Pacific Line Islands. To investigate patterns of parasitism, we trapped rats and quantified nematodes on 13 islets of various sizes and habitat types. Most rats were parasitized (59%) with an average of 12 worms per infected rat. Islet size did not greatly influence parasite population biology. Nematodes also did not appear to affect rat condition (weight to skull … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 12 publications
1
7
1
Order By: Relevance
“…Also in Hawai'i, ear mites (Notoedres muris) that cause ear lesions can infect 26% of the R. rattus population in some forests but other populations suffer very little (<2%) infection (Shiels 2010). Intestinal worms (helminths), likely the nematode Mastophorus muris, are common in wild R. rattus on many Pacific islands (Fall et al 1971, Sugihara 1997, Shiels 2010, and the majority of the R. rattus captured were parasitized by this worm on Palmyra Atoll ( Lafferty et al 2010) and on Rangitoto Island, New Zealand (Miller and Miller 1995). Because the nematodes M. muris and Physoloptera getula have obligate life cycles involving arthropods as intermediate hosts, R. rattus is likely infected directly by eating its arthropod prey (Miller and Miller 1995).…”
Section: Human Health Impactsmentioning
confidence: 99%
“…Also in Hawai'i, ear mites (Notoedres muris) that cause ear lesions can infect 26% of the R. rattus population in some forests but other populations suffer very little (<2%) infection (Shiels 2010). Intestinal worms (helminths), likely the nematode Mastophorus muris, are common in wild R. rattus on many Pacific islands (Fall et al 1971, Sugihara 1997, Shiels 2010, and the majority of the R. rattus captured were parasitized by this worm on Palmyra Atoll ( Lafferty et al 2010) and on Rangitoto Island, New Zealand (Miller and Miller 1995). Because the nematodes M. muris and Physoloptera getula have obligate life cycles involving arthropods as intermediate hosts, R. rattus is likely infected directly by eating its arthropod prey (Miller and Miller 1995).…”
Section: Human Health Impactsmentioning
confidence: 99%
“…In fact, Aedes is not the only putative secondary extinction associated with the Palmyra rat eradication. Most rats on Palmyra were parasitized with a rodent-specific stomach nematode [ 20 ], which must have also gone extinct on the atoll after rat eradication. These changes in the Palmyra food web show how removing introduced rats can have unintended indirect effects, including eradicating an introduced disease vector.…”
Section: Discussionmentioning
confidence: 99%
“…Forest type can affect parasites in other systems for unknown reasons. For instance, stomach nematodes in rats are more abundant in coconut plantations than native forests (Lafferty et al 2010). Previous studies have not found an effect of landscape type on nematomorphs (Hanelt et al 2001).…”
Section: Discussionmentioning
confidence: 99%